When do immigrant adolescents feel personally discriminated against? Longitudinal effects of peer preference. (May 2015) - Reitz, Anne K.; Asendorpf, Jens B.; Motti-Stefanidi, Frosso
Despite research showing that immigrant adolescents differ in the degree to which they feel personally discriminated against, little is known about individual predictors of their perceived personal discrimination. We studied the role of a major developmental task in adolescence that is highly relevant for discrimination experiences: being liked by peers. We followed N = 532 13-year old immigrant students ( n = 294 boys) in Greek high schools over 2 years to examine longitudinal links between personal ethnic discrimination and social preference among host-national and immigrant classmates. We applied a sociometric method to asses peer preference and we assessed self-perceived preference. Cross-lagged models revealed that preference among host-national peers but not by immigrant peers predicted low personal ethnic discrimination beyond self-perceptions of preference and group ethnic discrimination. Group ethnic discrimination moderated the effect of preference among host-national peers on low personal ethnic discrimination. Peer preference, in turn, did not feed back on personal ethnic discrimination. Findings highlight the importance of being liked by host-national classmates for immigrant adolescents: it can prevent feelings of being personally discriminated against, even if they perceive their group to be discriminated against.